STUDY OF ILLNESS BEHAVIOUR IN HYSTERICAL PATIENTS - Bhargava, S.C. (Medknow Publications, 1992)
Thirty patients diagnosed as Conversion Disorder and Somatization Disorder on DSM-III were investigated using IBQ and EPI. The patients differed with the controls on all the 7 factors of illness dimensions. They scored higher on neuroticism and low on extroversion.